(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
This research aims to show the sight at the importance of the private banking sector in Iraq and its role in financing of the investment projects , of the ability of Central Bank’s decision to increase the minimum limit of capital for private banks to provide support to the economic activity and the development in Iraq. In addition to illustrate the importance of the capital increase, with a, and taking into notice the most important determinants that can stand in front of these banks in the beginning of the decision implementation, which in turn can lead to the most important proceedings that can contribute in the support of banks to implementation the decision. Also, the research has highlighted the most important ways through which the banks can apply the decision and increase the minimum limit during the period specified for implementing the decision